COMPARATIVE STUDY OF VARIOUS INTERCALANT MODIFIED CLAY/RUBBER NANOCOMPOSITES PREPARED BY MELT-COMPOUNDING - Magdalena Lipińska (International Journal of Research Science and Management, 2017)
Rubbers are commonly compounded with different fillers in order to achieve the optimum of final properties. In studies layered silicates, montmorillonites, in natural and organically modified form were applied as reinforcing fillers for two rubbers differ in polarity, ethylene-propylene copolymer EPM and hydrogenated butadieneacrylonitrile rubber HNBR. The clay/rubber composites were prepared by melt-compounding method using various mixing conditions to obtain an optimal level of intercalated and exfoliated montmorillonite structures in peroxide cured rubber composites. The aim of this paper is to compare the influence of various types of montmorillonites on the rubber curing, crosslink density and mechanical properties of vulcanizates. Additionally, the effect of montmorillonites on weathering and UV ageing resistance of EPM rubber was determined